Using the PhenX Toolkit to Select Standard Measurement Protocols for Your Research Study. Issue 5 (26th May 2021) - Cox, Lisa Ann; Hwang, Stephen; Haines, Jonathan; Ramos, Erin M.; McCarty, Catherine A.; Marazita, Mary L.; Engle, Michelle L.; Hendershot, Tabitha; Pan, Huaqin (Helen); Hamilton, Carol M.
Abstract: The goals of PhenX (consensus measures for Phen otypes and eX posures) are to promote the use of standard measurement protocols and to help investigators identify opportunities for collaborative research and cross‐study analysis, thus increasing the impact of individual studies. The PhenX Toolkit (https://www.phenxtoolkit.org/ ) offers high‐quality, well‐established measurement protocols to assess phenotypes and exposures in studies with human participants. The Toolkit contains protocols representing 29 research domains and 6 specialty collections of protocols that add depth to the Toolkit in specific research areas (e.g., COVID‐19, Social Determinants of Health [SDoH], Blood Sciences Research [BSR], Mental Health Research [MHR], Tobacco Regulatory Research [TRR], and Substance Abuse and Addiction [SAA]). Protocols are recommended for inclusion in the PhenX Toolkit by Working Groups of domain experts using a consensus process that includes input from the scientific community. For each PhenX protocol, the Toolkit provides a detailed description, the rationale for inclusion, and supporting documentation. Users can browse protocols in the Toolkit, search the Toolkit using keywords, or use Browse Protocols Tree to identify protocols of interest. The PhenX Toolkit provides data dictionaries compatible with the database of Genotypes and Phenotypes (dbGaP), Research Electronic Data Capture (REDCap) data submission compatibility, and data collection worksheets to help investigators incorporate PhenX protocols into their study design. The PhenX Toolkit provides resources to help users identify published studies that used PhenX protocols. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Using the PhenX Toolkit to support or extend study design